1996
DOI: 10.1152/ajpgi.1996.271.1.g36
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY receptor in submucosal and myenteric plexus synaptosomes of canine small intestine

Abstract: PYY receptors were characterized and their loci determined in canine small intestine. The density of 125I-labeled peptide tyrosine tyrosine (PYY) binding was highest in myenteric (MY) and submucosal (SUB) plexus fractions enriched in synaptosomes. Two binding sites [high affinity (H) and low affinity (L)] were found in the submucosal synaptosome-enriched membrane: dissociation constant (Kd)H = 7.6 pM, maximal binding capacity (Bmax)H = 28 fmol/mg; KdL = 0.18 nM, BmaxL = 120 fmol/mg protein. The binding of 125I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The presence of Y1-R in the colon was confirmed by identification of a Y1-R-specific protein of 70 kD, corresponding to the previous published size of Y1-R (Sheikh and Williams 1990;Inui et al 1992;Mao et al 1996). Throughout the rat intestine, specific Y1-R immunoreactivity could be localized to many nerve cell bodies of the submucosal and myenteric plexi.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The presence of Y1-R in the colon was confirmed by identification of a Y1-R-specific protein of 70 kD, corresponding to the previous published size of Y1-R (Sheikh and Williams 1990;Inui et al 1992;Mao et al 1996). Throughout the rat intestine, specific Y1-R immunoreactivity could be localized to many nerve cell bodies of the submucosal and myenteric plexi.…”
Section: Discussionsupporting
confidence: 57%
“…Throughout the rat intestine, specific Y1-R immunoreactivity could be localized to many nerve cell bodies of the submucosal and myenteric plexi. Previous studies have also demonstrated the presence of NPY/PYY binding sites in submucosal and myenteric neurons by receptor autoradiography (Walsh et al 1993;Mao et al 1996). These studies, however, were not able to differentiate between NPY/PYY receptor subtypes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…NPY and PYY bind to and activate receptors Y 1 , Y 2 , and Y 5 , and PP binds to receptor Y 4 (Cox et al 2001;Cox and Tough 2002;Hyland and Cox 2005;Hyland et al 2003). Receptors Y 1 , Y 2 , and Y 4 have been found in the colon and small intestine, localized to epithelial cells and neurons belonging to the submucosal and myenteric plexus (Cox et al 2001;Cox and Tough 2002;Gregor et al 1996a;Gregor et al 1996b;Gue et al 1996;Inui et al 1992;Mao et al 1996;Sheikh and Williams 1990;Walsh et al 1993;Wharton et al 1993;Yan et al 1996).…”
Section: The Npy Family Of Peptidesmentioning
confidence: 99%
“…NPY-immunoreactive nerve fibers are abundant in GI tract (22,23). With the use of receptor autoradiography, NPY and peptide YY (PYY) binding sites have been localized to submucosal and myenteric plexi (30,45). In the GI tract, NPY and PYY have been shown to be potent inhibitors of intestinal fluid, electrolyte secretion, and motility (36, 38).…”
mentioning
confidence: 99%